UJI AKTIVITAS ANTIBAKTERI SEDIAAN MASKER CLAY DARI EKSTRAK DAUN KELOR ( Moringa Oliefera L. ) SEBAGAI SEDIAAN ANTI JERAWAT TERHADAP BAKTERI Staphylococcus Aureus ATCC 25923 - Rahmasari, Khusna Santika; Waznah, Urmatul; Slamet, Slamet; Mafruroh, Mafruroh (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Acne can disrupt appearance and cause discomfort due to pain. The bacteria that can cause acne is Staphylococcus aureus. Excessive or inappropriate use of antibiotics can lead to antibiotic resistance. One plant that has effectiveness as an antibacterial is Moringa leaves (Moringa Oliefera L.). The application of Moringa leaf extract as an antibacterial can be made into a clay mask preparation. The purpose of this study was to prove that Moringa leaf extract can be used as a clay mask and a clay mask preparation of Moringa leaf extract as an anti-acne against Staphylococcus aureus bacteria. Moringa leaf extract was obtained by maceration method with 96% ethanol solvent. The extract was formulated in the form of a clay mask with various concentrations of 15%, 20%, 25%. The results of the parameter tests included organoleptic, pH, homogeneity, spreadability, adhesiveness, viscosity and stability. Antibacterial activity tests were also carried out using the disc method. The research test of the inhibitory activity of the Moringa leaf extract clay mask showed good formula results at a concentration of 25% with an inhibitory diameter of 28.96 ± 0.43 mm. This study can be concluded that Moringa leaf extract can be formulated into a clay mask preparation and the resulting inhibition zone area with the clear zone area in Staphylococcus aureus bacteria.